OMBO-KAOMBO SEBAGAI BENTUK KEARIFAN LOKAL MASYARAKAT WABULA DALAM PENGELOLAAN SUMBER DAYA LAUT BERKELANJUTAN - Hasriyanti, Hasriyanti; Evita, Evita; Samiyem, Samiyem; Samsu, Taufiq Hidayat (UNIVERSITAS NEGERI MAKASSAR, 2024)
Indonesian society has sectors that must continue to be preserved and maintained, one of which is local wisdom. One of the local wisdoms in Indonesia is the local wisdom of the people in Buton Regency, namely the Wabula community. The aim of this research is to determine the sustainable management of marine resources in Buton Regency. Qualitative research through literature studies is used by researchers as a type in this research. This research covers an area, namely Wabula Village, Wabula District, Buton Regency. The documentation method is a data collection method used in research where written sources are tracked by researchers which contain various topics that are discussed and themes. The descriptive method is used to analyze the data that researchers collect so that what is being marketed can be explained by researchers. This research shows the results that the traditional local wisdom owned by the Wabula community has sustainable benefits in utilizing marine resources as a reflection of the kaombo system. Based on the concept related to Kaombo/Ombo by the Wabula people, there is a prohibition on the exploitation of marine resources for a certain period of time. The use of marine resources in Wabula which creates destructive practices can minimize the impact of existing customary sanctions. The pattern of marine resource utilization through the kaombo system supports the functional sustainability of the marine environment.